Structural and optical properties of ZnO thin films grown on flexible polyimide substrates - Son, Dong Ick; Lee, Jung Wook; Lee, Dea Uk; Kim, Tae Whan; Choi, Won Kook (WORLD SCIENTIFIC PUBL CO PTE LTD, 2007)
Nominally undoped ZnO thin films were grown on polyimide ( PI) substrates at various temperatures by using radio-frequency magnetron sputtering. Atomic force microscopy images showed that the root mean squares of the average surface roughnesses for the ZnO thin films grown on the PI substrates at 27 degrees C, 100 degrees C, 200 degrees C, and 300 degrees C were 4.08, 4.50, 4.18, and 3.89 nm, respectively. X-ray diffraction patterns showed that the crystallinity of the ZnO films had a preferential ( 0001) direction and that the full width at half-maxima for the ( 0002) ZnO diffraction peak for the ZnO thin films grown on the PI substrates at 27 degrees C, 100 degrees C, 200 degrees C, and 300 degrees C were 0.22, 0.22, 0.22, and 0.23, respectively. The average optical transmittances in the visible ranges between 550 and 750 nm for the ZnO/ PI heterostructures grown at 27 degrees C, 100 degrees C, 200 degrees C, and 300 degrees C were 87%, 83%, 87%, and 78%, respectively.
Keywords: SI